A ratiometric fluorescent probe for in situ quantification of basal mitochondrial hypochlorite in cancer cells - Hou, Ji-Ting; Li, Kun; Yang, Jin; Yu, Kang-Kang; Liao, Ye-Xin; Ran, Yu-Zhao; Liu, Yan-Hong; Zhou, Xue-Dong; Yu, Xiao-Qi (Chemical communications (Cambridge, England), 2015)
A ratiometric fluorescent probe ( RMClO-2 ) for ClO − based on the conjugate of coumarin–rhodamine was presented, which could sense ClO − with fast response (within 5 s), high sensitivity and excellent selectivity. More importantly, RMClO-2 is the first mitochondria-targeted ratiometric fluorescent probe to image exogenous and endogenous ClO − .